PENERAPAN MEDIA VIRTUAL LABORATORIUM DALAM PEMBELAJARAN BIOLOGI MATERI EUBACTERIA TERHADAP HASIL BELAJAR DAN KARAKTER SISWA - Dewi, Endah Rita Sulistya; Prasetiyo, Prasetiyo (BIOMA, 2015)
Virtual Laboratory Learning could be used to eliminate the limitationsof laboratory devices. A mix between the computer software which isdesigned to represent an alternative implementation concept of VirtualLaboratory. Through KD 3.4. Applying the Classification to classifyarchaebacteria and eubacteria based on characteristics and shapethrough systematic observation. It selected the Gram staining processin bacteria, which is to find groups of bacteria including GramPositive or Negative. The media influenced learning process in manysection, it is possible that the virtual lab used as a means to internalizethe values of character. This researchâs aim was to producedLaboratory Virtual Media Instruction, which was oriented formcharacter building through the development process. The method wasused research and development refers to the flow of Borg and Gall(1989). The results showed increasement in postal value, which isused Laboratory Virtual Media, compared to pre test, but the N-gainwas quite low at 0.2. Dicipline character, cooperation, honesty andaccuracy in good categories.Keywords: Virtual Laboratory, Eubacteria